Re-Conceptualizing Research: An Indigenous Perspective - Ormiston, Naadli Todd (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
This paper validates the differing in which Indigenous people are re-conceptualizing research as a form of decolonization, regeneration of cultures and communities, and ultimately self- determination. Indigenous people are taking control of their own destinies by providing needed solutions from within, as individuals, communities and Nations. This paper provides suggestions to indigenize the research process. This paper also includes principles provided by Irabinna (Dr. Lester Rigney) of Australia, the need to historicize, politicize, strategize and actualize our beings and our futures. Ultimately, the inspiration to write this paper comes from my Tlingit ancestors.